2020
DOI: 10.3390/ijms21165866
|View full text |Cite
|
Sign up to set email alerts
|

The Malignant Role of Exosomes as Nanocarriers of Rare RNA Species

Abstract: Nowadays, advancements in the oncology sector regarding diagnosis methods allow us to specifically detect an increased number of cancer patients, some of them in incipient stages. However, one of the main issues consists of the invasive character of most of the diagnosis protocols or complex medical procedures associated with it, that impedes part of the patients to undergo routine checkups. Therefore, in order to increase the number of cancer cases diagnosed in incipient stages, other minimally invasive alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 118 publications
1
27
0
Order By: Relevance
“…Two scaRNAs (SCARNA2 and SCARNA22) have been found to play an oncogenic role in colorectal cancer and multiple myeloma 22–24 . SNORD20 is reported as one of the most highly expressed RNAs in glioblastoma cell lines 8 . In another study, melanoma exosomes were found to be enriched with SNORD83A and SNORD89 25 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two scaRNAs (SCARNA2 and SCARNA22) have been found to play an oncogenic role in colorectal cancer and multiple myeloma 22–24 . SNORD20 is reported as one of the most highly expressed RNAs in glioblastoma cell lines 8 . In another study, melanoma exosomes were found to be enriched with SNORD83A and SNORD89 25 .…”
Section: Discussionmentioning
confidence: 95%
“…In general, novel sRNAs possess high stability and low variability, and are conserved across a range of species. Accordingly, they can be regarded as a more reliable source of non‐invasive biomarkers for the investigation of cancer than commonly used miRNAs or lncRNAs 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ExoCarta, an internet exosome database ( http://www.exocarta.org/ ), 286 studies identified 2838 miRNAs and 3408 mRNAs, respectively (June 2021). In addition to miRNAs and mRNAs, exosomes have also been documented to contain rRNAs, tRNAs, small Cajal body-specific RNAs (scaRNAs), small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), and piwi-interacting RNA (piRNA) from a previous investigation that assessed the exosomal content of exosomes derived from serum, plasma, urine, and Cerebrospinal Fluid [ 16 ]. Recently, exoRBase, a database developed by Fudan University Shanghai Cancer Center collected and characterized RNA species in human blood exosomes, and through RNA-sequencing data analyses and experimental findings from other literature, they detected 58,330 cirRNAs, 15,501 lncRNAs, and 18,333 mRNAs [ 17 ].…”
Section: The Profile and Sorting Of Rna Into Exosomesmentioning
confidence: 99%
“…For a detailed analysis on EV lncRNA-mediated crosstalk between tumor cells and the recipient cells in the TME, please refer to M. Zhang, Shi, et al (2020) andTellez-Gabriel &Heymann (2019). Additional studies have also identified other EVresident RNAs, such as small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), transfer RNAs (tRNAs), ribosomal RNAs (rRNAs), and piwi-interacting RNAs (piRNAs; Nolte-t' Hoen et al, 2012;Zimta et al, 2020). However, their detailed modes of action in recipient cells remain to be fully elucidated.…”
Section: Other Types Of Rnas In Extracellular Vesiclesmentioning
confidence: 99%